2019
DOI: 10.1186/s12939-019-0915-4
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic patterns of health insurance coverage in Namibia

Abstract: IntroductionHealth insurance has been found to increase healthcare utilisation and reduce catastrophic health expenditures in a number of countries; however, coverage is often unequally distributed among populations. The sociodemographic patterns of health insurance in Namibia are not fully understood. We aimed to assess the prevalence of health insurance, the relation between health insurance and health service utilisation and to explore the sociodemographic factors associated with health insurance in Namibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
9
24
1
Order By: Relevance
“…Consistent with previous studies [13,[15][16][17], the current study showed that the likelihood of being covered by health insurance was highest among educated women as compared with women with no education. The possible explanation could be educated women have more knowledge about the advantages of health insurance and make informed choices, engage themselves in different knowledge enhancement activities like reading materials, give more concern for their health and insure themselves against the unexpected out-of-pocket payments.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies [13,[15][16][17], the current study showed that the likelihood of being covered by health insurance was highest among educated women as compared with women with no education. The possible explanation could be educated women have more knowledge about the advantages of health insurance and make informed choices, engage themselves in different knowledge enhancement activities like reading materials, give more concern for their health and insure themselves against the unexpected out-of-pocket payments.…”
Section: Discussionsupporting
confidence: 92%
“…Even though, health insurance schemes designed to help ease the financial burden on the poorest households, the finding of this study revealed that the odds of health insurance coverage was higher among women in the richest wealth quintile. This finding is consistent with those from other settings elsewhere [13,[15][16][17]26]. This could be households with high wealth quantiles often have more income to afford health insurance premium compared to the poor once.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There are some studies in line with our findings. A study in Nambia concluded that sociodemographic factors (sex, education, and wealth) are associated with universal health care and financial coverage (45). Another study in Ghana also concluded that sociodemographic conditions (elders, women, poor education, and marginalized population) were associated with health services and financial coverage (46).…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated a higher utility from the dental services with higher cost coverage and the more preference for the dental care benefits insurance coverage among the more educated individuals. Similarly, a study in Namibia reported an association between educational status and health insurance, 40 and an association between more dental health-care services utilization and several factors including aging, having dental insurance, higher income, being a university graduate, self-rated poor oral health and not regularly brushing own teeth. 41 In Iran, there are different sources for the insurance of the health benefits packages.…”
Section: Discussionmentioning
confidence: 94%